Never Just Food: Themed Issue On Food And Asia - Tarulevicz, Nicole (Penerbit Universiti Sains Malaysia (USM Press), 2012)
At the time of writing this introduction, a food studies listserv run by the Association for the Study of Food and Society that I am on has been consumed by two threads: one has morphed into a "what is the state of the field" discussion and the other grapples with the crypto-Rumsfeldian question, "what don't we know about the food of the past." These are curiously relevant and timely questions for this themed issue on Food and Asia. We are in a moment of intense scholarly interest in how food is produced, consumed and understood. For many, there is an added urgency to the study of food as agribusiness and scientific developments change the very molecular composition of the foods we eat, and push some foods and foodways into the category of the permanently vanishing. In the context of the globalisation of food, the ongoing fears of a world-wide food crisis and the continuing inequalities of food production and consumption fuel this urgency. For those with an interest in the Asia Pacific region, these are particularly relevant issues.